A Chemiluminescent Probe for HNO Quantification and Real‐Time Monitoring in Living Cells. (21st December 2018) - An, Weiwei; Ryan, Lucas S.; Reeves, Audrey G.; Bruemmer, Kevin J.; Mouhaffel, Lyn; Gerberich, Jeni L.; Winters, Alexander; Mason, Ralph P.; Lippert, Alexander R.
Abstract: Azanone (HNO) is a reactive nitrogen species with pronounced biological activity and high therapeutic potential for cardiovascular dysfunction. A critical barrier to understanding the biology of HNO and furthering clinical development is the quantification and real‐time monitoring of its delivery in living systems. Herein, we describe the design and synthesis of the first chemiluminescent probe for HNO, HNOCL‐1, which can detect HNO generated from concentrations of Angeli's salt as low as 138 nm with high selectivity based on the reaction with a phosphine group to form a self‐cleavable azaylide intermediate. We have capitalized on this high sensitivity to develop a generalizable kinetics‐based approach, which provides real‐time quantitative measurements of HNO concentration at the picomolar level.HNOCL‐1 can monitor dynamics of HNO delivery in living cells and tissues, demonstrating the versatility of this method for tracking HNO in living systems.